Evaluation of Implementation of Search Engine Optimization are on Site and off Site on E-Commerce Website PT Puncak Finansial Utama - Septiano Anggun Pratama (International Journal of Computer and Information System (IJCIS), 2026)
This research aims to do optimization potential that can be obtained by cekaja.com. The problems faced by cekaja.com is the low visitor traffic in terms of quality and quantity, as well as the lack of a landing page for some of the products sold on the website cekaja.com. Methods undertaken to analyze the SEO work is done before by doing data collection of visitor traffic 3 – 6 months earlier using google analytics. Then also do basic keyword searches of the work SEO with the google keyword tools. After that traffic visitors observation was undertaken based on the results that have been implemented in terms of the intended landing pages and also the quality and quantity of searches using google analytics. Analysis of the results of this research brings about problems of search traffic is low, the length of time a little visit, the value of a high bounce rate, low organic search on the site, and from it all the troubleshooting can be done with the implementation of SEO. Thus SEO deserves to be implemented on every newly built website as well as websites that have low search traffic in order to have a good visit value.